The Role of Translanguaging In English Language Teaching in Indonesian Multilingual Context: A Literature Review - Anggraeni Khusuma Dewi Anggraeni; Muhammad Haikal Attabik; Mailiza Zainiza (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
This literature review explores the role of translanguaging in English Language Teaching (ELT) within Indonesia’s multilingual context. As a country with over 700 regional languages, Indonesia presents a linguistically complex educational landscape that challenges traditional monolingual paradigms. Drawing upon eleven recent empirical and theoretical studies published between 2023 and 2025, this review identifies the pedagogical benefits, strategies, teacher and student attitudes, and challenges of implementing translanguaging in EFL classrooms. The findings indicate that translanguaging enhances students’ conceptual understanding, linguistic confidence, and classroom participation by leveraging their full linguistic repertoires. Common strategies include bilingual discussions, L1 scaffolding, and multimodal teaching. Despite its demonstrated effectiveness, resistance persists among some educators due to entrenched monolingual ideologies. The study underscores the need for curriculum reform and professional development that incorporates translanguaging principles to build a more inclusive and context-sensitive ELT framework. It concludes that translanguaging is not merely a teaching strategy but a transformative practice that promotes linguistic justice and sustainable language education in Indonesia.